TYPE 2 DIABETES MELLITUS AND CHRONIC KIDNEY DISEASE : A SYSTEMATIC REVIEW - Frida Setiawan, Yenny (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Hyperglycemia is the primary symptom of diabetes mellitus, which is a set of metabolic illnesses that can be caused by abnormalities in insulin secretion, insulin action, or both. Diabetes Mellitus (DM) is the most common form of diabetes. Chronic hyperglycemia brought on by diabetes is linked to long-term damage, dysfunction, and even failure of a number of glands, most notably the eyes, kidneys, nerves, heart, and blood arteries. 1 Because there are a variety of criteria that must be satisfied before a diagnosis of diabetes can be made, it is challenging to estimate the disease's prevalence. Diabetes-related nephropathy, also known as diabetic nephropathy or diabetic kidney disease, can affect approximately forty percent of patients who have been diagnosed with type 2 diabetes mellitus (DKD). Patients who are diagnosed with type 2 diabetes are often of an older age at the time of their diagnosis, and it is possible that these patients will develop kidney damage due to factors other than diabetes. Patients diagnosed with type 2 diabetes are at an increased risk of developing chronic kidney disease (CKD) due to a number of variables, including hypertension, a history of kidney disease, neuropathy, dyslipidemia, and substance abuse.